Alterations in sulcal depth and associated functional connectivity in schizophrenia with auditory verbal hallucinations - Guo, Zhenru; Zhou, Zimo; Wang, Shuai; Yang, Lianlian; Gao, Xiaoshan; Xia, Yu; Yang, Yuanyuan; Shan, Zhangyan; Huang, Haixia; Tian, Lin (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia patients with auditory verbal hallucinations exhibit brain structure abnormalities. However, the characterization of sulcal depth alterations and associated functional connectivity across the whole brain remains unclear.MethodWe recruited 38 schizophrenia patients with auditory verbal hallucinations and 31 schizophrenia patients without auditory verbal hallucinations. Magnetic resonance imaging data were collected on all participants, and clinical symptoms were assessed using standardized clinical scales. Structural abnormalities identified through sulcal depth analysis were localized to specific brain regions, which were subsequently selected as seed regions for functional connectivity analysis. Correlation analysis was employed to explore the associations between sulcal depth, functional connectivity, and the severity of clinical symptoms in individuals with schizophrenia with auditory verbal hallucinations.ResultsSchizophrenia patients with auditory verbal hallucinations exhibited significantly increased sulcal depth in left hemispheric regions including the lingual gyrus, cingulate gyrus, pericalcarine cortex, parahippocampal gyrus, superior frontal gyrus, cuneus, and precuneus, whereas decreased sulcal depth was observed in right hemispheric regions encompassing the superior parietal gyrus, superior frontal gyrus, lingual gyrus, lateral occipital cortex, fusiform gyrus, postcentral gyrus, middle frontal gyrus, precentral gyrus, inferior temporal gyrus, precuneus, and parahippocampal gyrus compared to schizophrenia patients without auditory verbal hallucinations. Seed-based functional connectivity analysis revealed widespread weakened connectivity in schizophrenia patients with auditory verbal hallucinations, particularly with the superior frontal gyrus, angular gyrus, putamen, and other regions. The increased sulcal depth cluster in schizophrenia patients with auditory verbal hallucinations was significantly correlated with negative syndromes and general psychopathology of Positive and Negative Syndrome Scale.ConclusionThese findings highlight sulcal depth and associated functional connectivity abnormalities in schizophrenia patients with auditory verbal hallucinations, implicating early neurodevelopmental disturbances involving the default mode network and visual cortex. Sulcal depth may represent a promising biomarker for early diagnosis.